2018
DOI: 10.7196/samj.2018.v108i9.13317
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric hypertension in South Africa: An underestimated problem calling for action

Abstract: This open-access article is distributed under Creative Commons licence CC-BY-NC 4.0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…As such, although we are confident in our results, our findings do not reflect clinical prevalence rates. It is crucial for future research that South Africa joins ongoing work to create international blood pressure references, measurement guidelines and appropriate cut-points for defining hypertension, particularly for children [4].…”
Section: Discussionmentioning
confidence: 99%
“…As such, although we are confident in our results, our findings do not reflect clinical prevalence rates. It is crucial for future research that South Africa joins ongoing work to create international blood pressure references, measurement guidelines and appropriate cut-points for defining hypertension, particularly for children [4].…”
Section: Discussionmentioning
confidence: 99%
“…As new research emerges, we are gaining awareness of the extent of a long underappreciated problem and the consequences of its (mis)management, such as impaired development, economic burden, years of life lost, etc. ( 5 ). A recent meta-analysis revealed that global hypertension rates among children have increased about 75% over the past 20 years ( 6 ), which has been partially attributed to the steep escalation in childhood obesity, an early-life risk factor for CVD.…”
Section: Introductionmentioning
confidence: 99%
“…elevated blood pressure) [6][7][8][9][10] . Hypertension is the largest contributor to CVD in Africa, with research showing elevated blood pressure in children as young as 5 years of age 11 . Studies of mono-and dizygotic twins have shown high heritability of systolic and diastolic blood pressure in populations of both African and European decent 12 13 , though heritability may be lower for individuals of African decent 14 .…”
Section: Introductionmentioning
confidence: 99%